Oxidative Stress in Patients With Nongenital Warts - Sezai Sasmaz; Ozer Arican; Ergul Belge Kurutas (Hindawi Limited, 2005)
Comparison of oxidative stress status between subjects with or without warts is absent in the literature. In this study, we evaluated 31 consecutive patients with warts (15 female, 16 male) and 36 control cases with no evidence of disease to determine the effects of oxidative stress in patients with warts. The patients were classified according to the wart type, duration, number, and location of lesions. We measured the indicators of oxidative stress such as catalase (CAT), glucose-6-phosphate dehydrogenase (G6PD), superoxide dismutase (SOD), and malondialdehyde (MDA) in the venous blood by spectrophotometry. There was a statistically significant increase in levels of CAT, G6PD, SOD activities and MDA in the patients with warts compared to the control group (P<.05). However, we could not define a statistically significant correlation between these increased enzyme activities and MDA levels and the type, the duration, the number, and the location of lesions. We determined possible suppression of T cells during oxidative stress that might have a negative effect on the prognosis of the disease. Therefore, we propose an argument for the appropriateness to give priority to immunomodulatory treatment alternatives instead of destructive methods in patients with demonstrated oxidative stress.